Kajian Residu Sulfamonometoksin Dosis Pencegahan terhadap Leucocytozoonosis dalam Telur Ayam Ras = Study on Residu of Leucocytozoonosis Preventive Doses of Sulphatnonomethoxine in Layer's Egg - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
One of the Indonesian government efforts to fulfill animal protein need was improving poultry husbandry especially laying hens. Among the obstacles faced by the farmers was leucocytozoonosis. The disease could be prevented by either eradicating its vector or daily administration of 30-50 ppm sulphamonomethoxine for 10-15 consecutive days or both. The last method, however, may create residue problem in eggs produced by the hen. The objective of this study was to detect this residue in the eggs and to determine the correct withdrawal time of the drug. Eight laying hens (Isa-Broitm strain), weighing about 1,500 g, age of 28 weeks, were equally allocated randomly into 2 groups and kept in individual cages. Two weeks before the treatment, the hens were fed without the drug. Water was given ad libitum. The first and second groups were received feed containing 30 and 50 ppm of sulphamonomethoxine for 10 consecutive days. The eggs produced were collected daily for 4 days following the last administration of the feed. The concentration of sulphamonomethoxine in the albumine was analysed in high performance liquid chromatography (HPLC). Concentration of sulphamonomethoxine lower than 0.1 ppm of egg was detected on the first day after the last administration. It indicated no residue problem for the consumers.